MEMBANGUN WIRAUSAHA MUDA BAGI PESERTA PELATIHAN DI LKP FLORENZA KABUPATEN DEMAK - Wahyuningsih, Susanti; Widodo, Untung; Indriyatni, Lies; Yuliati, Yuliati; Prabowo, Janitra; Damayanti, Damayanti; Ainiyah, Ghonimah Zumroatun (Fokus ABDIMAS, 2024)
This community service aims to broaden the perspectives and motivate participants of LPK Florenza in Demak Regency to become competent and successful entrepreneurs, so they can support themselves without depending on others, in accordance with the principles of management and accounting. The methods used include lectures, workshops, and mentoring in starting a business. Based on the results of the community service conducted at LPK FLORENZA, there is a lack of motivation to be creative and a lack of understanding of managing financial reports and tax reports correctly, often leading to fear of becoming an entrepreneur. The conclusion that can be drawn is the importance of providing training on building effective individuals and understanding business ethics, being able to manage financial reports and understand tax reports properly for each participant so that they can cultivate an interest in becoming an entrepreneur and be able to run their businesses without fear due to lack of knowledge. Thus, the training participants can become competent entrepreneurs. Keyword : Building effective individuals, Enterpreuner , Business ethics, Managing financial reports and Tax reports